HMGB1: A Potential Target of Nervus Vagus Stimulation in Pediatric SARS-CoV-2-Induced ALI/ARDS - Jankauskaite, Lina; Malinauskas, Mantas; Mickeviciute, Goda-Camille (Frontiers in Pediatrics, 2022)
From the start of pandemics, children were described as ones who were less affected by SARS-Cov-2 or COVID-19 was mild in most of the cases. However, with the growing vaccination rate of the adult population, children became more exposed to the virus and more cases of severe SARS-CoV-2 induced ARDS are being diagnosed with the disabling consequences or lethal outcomes associated with the cytokine storm. Thus, we do hypothesize that some of the children could benefit from nervus vagus stimulation during COVID-19 ARDS through the inhibition of HMGB1 release and interaction with the receptor, resulting in decreased neutrophil accumulation, oxidative stress, and coagulopathy as well as lung vascular permeability. Moreover, stimulation through alpha 7nicotinic acetylcholine receptors could boost macrophage phagocytosis and increase the clearance of DAMPs and PAMPs. The further rise of FGF10 could contribute to lung stem cell proliferation and potential regeneration of the injured lung. However, this stimulation should be very specific, timely and of proper duration, as it could lead to such adverse effects as increased viral spread and systemic infection, especially in small children or infants due to specific pediatric immunity state and anatomical features of the respiratory system.